2019
DOI: 10.1248/bpb.b19-00404
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rac1 Activation in the Enhanced Carbachol-Induced Bronchial Smooth Muscle Contraction of Repeatedly Antigen-Challenged Mice

Abstract: Recently, we demonstrated that Rac1 upregulation is involved in augmented bronchial smooth muscle (BSM) contractions of antigen-challenged mice. However, change in G protein-coupled receptor (GPCR)induced Rac1 activation remains unknown in BSMs of repeatedly antigen-challenged (Chal.) mice. We here examined carbachol (CCh)-induced Rac1 activation in BSMs of Chal. mice. Gene expression levels of both Rac1 and Rac-guanine nucleotide exchange factors (GEFs), such as Tiam1 and Trio, were increased in BSMs of Chal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…2013; Kai et al . 2019 a ). NSC23766 blocked EPS‐induced increases in β‐catenin S675 and PAK T423 phosphorylation but did not alter p38 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…2013; Kai et al . 2019 a ). NSC23766 blocked EPS‐induced increases in β‐catenin S675 and PAK T423 phosphorylation but did not alter p38 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2015; Kai et al . 2019 a , b ). Carbachol induced phosphorylation of both PAK T423 and β‐catenin S675 , but not β‐catenin S552 in C2C12 myotubes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we tested whether the constitutive activation of RAC1 was sufficient to rescue the phenotypes induced by myosin VI depletion using different orthogonal approaches. First, we found that the addition of cholinergic agonist and RAC1 activator carbachol [41, 42] partially rescued the wound closure defect observed upon myosin VI depletion (Figure S3D). Next, we expressed RAC1 wild-type (WT-RAC1) or its fast cycling RAC1-P29S variant [43] in EGFP-LifeAct-expressing cells after silencing of myosin VI.…”
Section: Resultsmentioning
confidence: 98%